2004
DOI: 10.1080/00365540410019354
|View full text |Cite
|
Sign up to set email alerts
|

Primary Herpes simplex Virus Type 1 Gingivostomatitis During the Second and Third Trimester of Pregnancy: Foetal and Pregnancy Outcome

Abstract: Primary herpetic gingivostomatitis during pregnancy is a relatively rare phenomenon with no clear management guidelines. We describe 4 cases of primary herpetic gingivostomatitis during pregnancy and review the literature. The diagnosis in all cases was based on clinical manifestations and serology and culture findings. Two of the women received intravenous rehydration. Acyclovir, offered in 2 cases, was refused. Delivery was normal in all 4 cases, with good neonatal outcome, similar to findings in the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A review of the literature of clinical outcomes of neonates born to mothers with documented primary HSV gingivostomatitis during pregnancy or at the time of delivery is limited to a few case reports, as summarized in Table 2 [1,[8][9][10][11]. In contrast to our case series, no adverse neonatal outcome was noted in the previously reported cases.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…A review of the literature of clinical outcomes of neonates born to mothers with documented primary HSV gingivostomatitis during pregnancy or at the time of delivery is limited to a few case reports, as summarized in Table 2 [1,[8][9][10][11]. In contrast to our case series, no adverse neonatal outcome was noted in the previously reported cases.…”
Section: Resultsmentioning
confidence: 68%
“…In addition, all previous case reports and series published up until now have indicated that primary maternal HSV-1 gingivostomatitis during pregnancy is not associated with adverse neonatal outcomes [1,[7][8][9][10]. However, given the identified adverse neonatal outcomes seen in our review, treating physicians should apply close monitoring practices and have a low threshold for prompt evaluation and treatment of these at-risk neonates.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Neonatal infection can be transmitted from the mother antepartum, but acquisition is most likely intrapartum during passage through the birth canal, in mothers with primary genital herpes infection, most often with type HSV-2 rather than HSV-1. A recent report of four cases of primary herpetic gingivostomatitis during the second and third trimester of pregnancy supports the notion that peripartum oral infection in the mother does not pose a significant risk for neonatal infection, but additional studies are needed to explore the extent of this type of risk [17].…”
Section: Primary Herpetic Gingivostomatitis and Recurrent Herpes Labimentioning
confidence: 90%
“…Herpes simplex virus (HSV) is a widespread pathogen that has diverse clinical manifestations ranging from mild to severe diseases leading to death, for example, cold sores, herpetic whitlow, gingivostomatitis, and neonatal herpes (Berkovich and Ressel, 1966;Crane and Lerner, 1978;Pardo et al, 2004;Slifer and Jennings, 2015). HSV belongs to the family Herpesviridae, subfamily Alphaherpesvirinae.…”
Section: Introductionmentioning
confidence: 99%